Molecular identification of the brown marmorated stink bug’s egg parasitoids by species-specific PCR collected from Beijing, China - Muhammad Yasir Ali; Yu-Di Liu; Feng-Qi Li; Mao-Lin Hou; Jin-Ping Zhang; Feng Zhang (CABI Agriculture and Bioscience)
Abstract Brown marmorated stink bug (BMSB), Halyomorpha halys (Stål) (Hemiptera: Penta-tomidae), is a highly polyphagous and invasive insect pest with more than 300 plant species as hosts, including a wide range of economic crops. To date, several egg parasitoid species are reported to attack BMSB. In this study, two species of Trissolcus (Hymenoptera: Platygastridae) and one Anastatus (Hymenoptera: Eupelmidae) were recovered from field exposed BMSB sentinel eggs in Beijing, China. The wasps’ small size of only 1.5 mm and 4 mm in length make them difficult to identify morphologically and required taxonomist for identification of specific species. In addition, these parasitoids have morphology sibling species and have been misidentified several times in China. To overcome these problems, a molecular method with species-specific primers designed for the COI gene has been developed to identify Trissolcus, Anastatus and their host samples from field collected samples. After successful morphological confirmation with experts, DNA extractions were carried out from these samples. PCR amplification using published primers for T. japonicus, A. japonicus and BMSB specimens confirmed the species. As for T. cultratus, species specific primers TCYF and TCYR were developed which produce 340-bp PCR products length while no positive amplifications found in other wasps and host. Sensitivity analysis of markers revealed that TCYF and TCYR primers could detect as low a DNA template concentration as 0.00025 ng/μL. This indicates that PCR with these primers specifically and sensitively differentiates T. cultratus specimens from other similar wasp species. All the primers tested in this study could discriminate between parasitized and non-parasitized BMSB eggs. This molecular identification method shows promise for conveniently identifying Trissolcus and Anastatus species in host-parasitoid associations and accurately evaluating parasitism rates in the field.